2001
DOI: 10.1007/s10434-001-0138-x
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer After Augmentation Mammoplasty

Abstract: Augmented patients were more likely to have palpable cancers, although the overall stage and outcome were similar to those of nonaugmented women. Although there have been significant improvements in our ability to diagnose early breast cancer over the past two decades, mammography continues to be suboptimal in augmented women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 26 publications
0
24
1
2
Order By: Relevance
“…The study concluded that the presence of minimal capsular contracture resulted in a 30% reduction in visualized breast tissue, whereas moderate or severe capsular contracture led to a 50% decrease. In support of these findings, Skinner et al (16) found that augmented women were more likely to present with palpable cancers rather than mammographic abnormalities, as compared to nonaugmented women (83% versus 59%), although the overall stage and outcome were similar in both groups.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The study concluded that the presence of minimal capsular contracture resulted in a 30% reduction in visualized breast tissue, whereas moderate or severe capsular contracture led to a 50% decrease. In support of these findings, Skinner et al (16) found that augmented women were more likely to present with palpable cancers rather than mammographic abnormalities, as compared to nonaugmented women (83% versus 59%), although the overall stage and outcome were similar in both groups.…”
Section: Discussionmentioning
confidence: 86%
“…Consistent with the above referenced studies, our results may indeed represent a reduced sensitivity of mammography, as influenced by a reduction in visualized breast tissue, the inability of radiologists to identify tumors in the presence of an implant, or the rate of tumor growth between screening examinations (18). In addition, the increased proportion of palpated tumors in our cohort may also be attributed to decreased breast volume in the presence of an underlying firm implant to palpate against (16,17,19,20). This, in combination with a potential for increased breast/body awareness in augmented women, may further enhance the utility of the breast examination (16,17,19,20).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…A formal evaluation of whether implants delay the detection of breast cancer among women with breast implants can be made by comparing their stage distribution at diagnosis to a suitable comparison group. While a few studies have performed such evaluations, their findings have been mixed with some reporting that women with breast augmentation may be more likely to be diagnosed with advanced cancers5, 18–21 while others have reported no such difference 4, 8, 22–28. Most of these studies have been severely limited by a small number of incident breast cancers.…”
mentioning
confidence: 99%
“…22,23,[32][33][34] Others have shown that women with implants had larger primary tumors, more positive axillary nodes, or a lower percentage of palpable tumors visible on mammography than comparison groups of women without breast implants. 17,[35][36][37] Because of the relatively young age of the women in these studies, screening mammography may not have been performed routinely in this subgroup of patients.…”
Section: Breast Cancer Stage At the Time Of Detectionmentioning
confidence: 96%